The influence of triplet states in organic photovoltaics - Clarke, Tracey (My University, 2023)
Triplet formation is generally regarded as an energy loss process in organic photovoltaics. Understanding charge photogeneration and triplet formation mechanisms in non-fullerene acceptor blends is essential for deepening understanding of photophysics in these important organic photovoltaic materials. In this talk, the methods of creating triplet states in organic photovoltaic materials and blends are covered. I also discuss if the appearance of these triplets states are either a hindrance or a help with actual experimental examples. We infer extending triplet lifetimes by new triplet formation mechanisms, checking their differences if they were created either on ultrafast or microsecond timescales, and quantifying their populations.
Keywords: Espectroscopía; Organic electronics; Spectroscopy